Representasi Kaum Difabel dalam Piala Dunia Qatar 2022 : (Analisis Isi Video pada Akun Youtube Sport News 21 November 2022) - Devina Melinawati; Tutut Nur Trias Wijayanti; Nadhiroh (Jurnal Jurnalisa: Jurnal Jurusan Jurnalistik, 2023)
The Qatar 2022 World Cup presents a different view than the previous one. The presence of one of the World Cup ambassadors, Ghanim Al Muftah, at the opening of this prestigious football event brought a different atmosphere. This article attempts to explore the representation of disabled people at the 2022 Qatar World Cup to Show Islam Rahmatan Lil'alamin. The research approach used is qualitative with descriptive content analysis methods. The content analysis examines the content in the sample video from the Sport News YouTube account on 21 November 2022. In Ghanim Al Muftah's appearance on the principles of depicting people with disabilities in 'Disabling Imagery and The Media' by Collin Barnes, namely: 'disability language and terminology ', 'how disability is portrayed', and 'portrayal of disabled people in advertising'. The research results show that (1) The use of language and terms in the opening of the 2022 Qatar World Cup reflects the equal rights of people in a social context to appear in public; (2) People with disabilities in this broadcast have been depicted accurately and are 'multifaceted' using progressive framing. (3) In the advertising context, the show has used people with disabilities in product placement and brand integration by depicting the involvement of people with disabilities in major events like the World Cup. The appearance of people with disabilities plays a role in showing that Islam is Rahmatan lil'alamin.